Działalność Ośrodka Badań nad Geografi ą Historyczną Kościoła w Polsce KUL - Mielnik, Sławomir (Archiwa, Biblioteki i Muzea Kościelne, 2011)
In 2010 the University Senate decided to include the Institute for the Historical Geography of the Church in Poland, established in 1957 by prof. Jerzy Kłoczowski, in the structures of the Faculty of Humanities and changed its name into the Research Centre for the Historical Geography of the Church in Poland. Thanks to this decision, the Lublin centre, which has a few dozen years of tradition dating back to the most difficult times of the Polish People’s Republic, has the opportunity to continue the research on the history of Churches and religions in Poland. The article presents the outline of the Centre (Institute) activity, its achievements and the main research goals. The presentation of the Centre activity from a chronological perspective is an attempt to show the intricacy of the research issue and the development of the research into the historical lands of Poland from religious, social and demographical point of view. Presenting the most important achievements of workers and coworkers enabled to show the scope of research concerning territorial structures of major and minor Churches, male and female congregations, especially the activity of female congregations during the Second World War and in the Polish People’s Republic, social and demographic issues, and others. Showing the history and achievements of the Centre also serves as a reminder of the role it played and still plays in the research on the history of churches, religions, faiths in the former Republic of Poland and the East-Central Europe. The synthetic presentation of the problems connected with the historical geography and cartography of the Church is also an attempt to assess the possibilities of further development of the research on geography, and social and religious history in Poland.